PEMANFAATAN MEDIA SOSIAL DALAM MEMBANGUN EKSISTENSI KOMUNITAS TRUE BLUE INDONESIA - ., Wahyudi (JURNAL KOMUNITAS, 2016)
The objective of this study was to examine the use of social media in building community existence True Blue Indonesia based on the theory of mass communication functions MacBridge. This study used a qualitative method with descriptive qualitative approach, which is a research procedure using descriptive data in the form of words written or spoken of people and offenders can be observed. The object of this study is a community of True Blue Indonesia with datasource comes from informants consisting of 2 Board of Directors (BoD) True Blue Indonesia, 1 Chief Operating Officer (COO) Blues Troops, 7 person board zones True Blue Indonesia, and 6 an active member of True Blue Indonesia as well as through the documentation. Data collection techniques used were interviews, observation, and. While the technical validity of the data used atriangulation of data sources. The result, utilization of social media in establishing the existence of the community do True Blue Indonesia effective. Exploiting social media fulfill the function of information, socialization, motivation, debate, discussion, education, entertainment, and integration. The function of mass communication through social media in establishing the existence of a community of True Blue Indonesia effective because attention to the characteristics of social media, the characteristics of social media, and attention to those aspects that can assist in the use of social media becomes more effective as set targets and types of social media that will in use, the power of creative content, to establish effective communication in person, and look for the right party.